GRANULASI LUMPUR BIOGAS ANAEROBIK - Djoko Padmono (Jurnal Teknologi Lingkungan, 2007)
This article contained several differences of the theory about anaerobicsludge granulation biogas in the UASB reactor. The level of the granulationformation of the beginning followed same principles as the formation bio-film from the bacteria to a surface field. There exist strong facts that thematerial inert played a positive role important and granulation. Mostresearchers took the conclusion that Methanosaeta concilii was the mainkey to the formation of granulation. Only Town Stamp hypotheses thatassumed that the organism autotrophic hydrogenotrophic like for exampleMethanobacterium from strain AZ, could grow in the condition high H2-pressure, was the key to the formation organism of granulation. Severalwriters focus in the stage granulation early and only several contributionsthat discussed the following stage in granulation included maturationgranulation and multiplication. Determining factors granular in the latterstage was dominated in the existence of the manipulation of the pressureelection, through which particle of bigger sludge selectively was kept inthe UASB reactor.